The Synergistic Effects of Periodontal Regeneration and Orthodontic Techniques on Clinical Outcomes: A Systematic Review - S. M. Karthickraj; Suchareeta Panda; Purnima Nadkerny; Ankur Jethlia; Sreeshyla Huchanahalli Sheshanna; Muzammil Moin Ahmed (Journal of Head & Neck Physicians and Surgeons)
Background: The integration of orthodontic techniques with periodontal regeneration has been hypothesized to enhance clinical outcomes in periodontal treatment. This systematic review aimed to evaluate the synergistic effects of these combined therapies on clinical and patient-reported outcomes. Materials and Methods: A comprehensive literature search was conducted using PubMed, Embase, Web of Science, Scopus, Cochrane Library, and Google Scholar. Relevant studies were selected based on predetermined inclusion and exclusion criteria. The data extraction was performed by two independent reviewers using a standardized form, which was pretested on a subset of included studies. Discrepancies were resolved through discussion or by a third reviewer. Results: We identified 6 studies that collectively emphasized the significant benefits of combining orthodontic interventions with periodontal regeneration. The studies reported enhanced clinical outcomes, including better inflammation control, improved periodontal health, and accelerated recovery processes. Some studies highlighted the importance of timing and direction of orthodontic forces postperiodontal surgery, indicating that these factors are crucial for optimizing periodontal regeneration. Long-term benefits of such combined treatments were also documented, showing sustained improvements over several years. Conclusion: The findings suggest that the combination of orthodontic techniques and periodontal regeneration therapies significantly improves clinical outcomes and patient satisfaction. Strategic planning regarding the timing and application of orthodontic forces can further enhance these effects. Long-term follow-up confirms the sustained benefits of these integrated treatment approaches.